Estudo epidemiologico do complexo teníase-cisticercose: nova abordagem - Aragão, Samuel Carvalho de [UNESP] (2014)
Bovine cysticercosis is the main cause of carcass condemnation in the Brazilian beef cattle industry and it is responsible for large economic losses in the meat production chain. Up to now, there is no commercial vaccine in Brazil or a more effective anthelmintic to control this disease. This problem is impaired by the Brazilian beef cattle production system as well as by the epidemiological characteristics of this zoonosis, where the man plays an important role for its transmission to cattle. Based on the perspective of better controlling this disease. the present study aimed to construct a cattle movement network and a map of bovine cysticercosis ocurrecnce in the Mato Grosso do Sul state, based on data of the Animal Movement Permits and of bovine cysticercosis carcass condemnation. This approaches allowed us to analyze the diseases' distribution, to identify areas of high occurrence and to suggest punctual control measures minimizing the economic losses this disease causes in its production chain